Education Problems in the Lebanese Parliament 1943-1945 - Jasem Al. Subaihi, Qutaiba Ali (Journal of Tikrit University for Humanities, 2023)
The research talks about the problems of education in Lebanon during the era that followed the declaration of Lebanon’s independence from November 1943 until the end of the Second World War in 1945. The second cabinet, led by Abdel Hamid Karami, had the most prominent role in addressing these problems through the reforms witnessed by the Lebanese Parliament.